Impact of H‐Uptake from Forming Gas Annealing and Ion Implantation on the Photoluminescence of Si Nanoparticles. Issue 3 (12th October 2017) - Chulapakorn, Thawatchart; Primetzhofer, Daniel; Sychugov, Ilya; Suvanam, Sethu Saveda; Linnros, Jan; Hallén, Anders
Abstract : Silicon nanoparticles (SiNPs) are formed by implanting 70 keV Si + into a SiO2 ‐film and subsequent thermal annealing. SiNP samples are further annealed in forming gas. Another group of samples containing SiNP is implanted by 7.5 keV H + and subsequently annealed in N2 ‐atmosphere at 450 °C to reduce implantation damage. Nuclear reaction analysis (NRA) is employed to establish depth profiles of the H‐concentration. Enhanced hydrogen concentrations are found close to the SiO2 surface, with particularly high concentrations for the as‐implanted SiO2 . However, no detectable uptake of hydrogen is observed by NRA for samples treated by forming gas annealing (FGA). H‐concentrations detected after H‐implantation follow calculated implantation profiles. Photoluminescence (PL) spectroscopy is performed at room temperature to observe the SiNP PL. Whereas FGA is found to increase PL under certain conditions, i.e., annealing at high temperatures, increasing implantation fluence of H reduces the SiNP PL. Hydrogen implantation also introduces additional defect PL. After low‐temperature annealing, the SiNP PL is found to improve, but the process is not found equivalently efficient as conventional FGA. Abstract : Hydrogen concentrations in a SiO2 matrix containing Si‐nanoparticles is probed by performing nuclear reaction analysis . Forming gas annealing and H‐implantation are employed to introduce hydrogen in order to neutralize dangling bonds commonly found at a SiO2 /Si–nanoparticle interface. It is found that H‐uptake related to an increase in luminescence of Si‐nanoparticles, is found to be lower than 60 ppm.